PHYTOBIOTIC ACTIVITY OF Larrea tridentata, Origanum vulgare AND Plectranthus amboinicus IN GRAM POSITIVE AND GRAM NEGATIVE BACTERIAS - Itza Ortiz, Mateo Fabian (2019)
The objective of the study was to evaluate the phytobiotic activityof Larrea tridentata, Origanum vulgare and Plectranthus amboinicus on Gram positive and Gram negative bacteria of common presence that endanger human health directly or indirectly. Extracts of leaves from each of the three plants under study were prepared in 75% ethyl alcohol, in proportions of 30, 35 and 40%, for a total of nine treatments. The bacterial strains were divided into two groups, depending on their staining properties: Gram (+) and Gram (-). The response variable was the size if the inhibition halo of bacterial growth. The data was analyzed using the Kruskal-Wallis test. Differences were found (P<0.05) in the type of extract, concentration level and type of bacteria, as well as in the interaction of the extract and level (P<0.04), and in the interaction of extract, level and bacteria (P<0.002). It is concluded that L. tridentata at 35% had a higher phytobiotic activity, compared with O. vulgare and P. amboinicus.